HUBUNGAN KEKUATAN OTOT PUNGGUNG DENGAN KELUHAN NYERI PUNGGUNG PADA PORTER DI STASIUN TAWANG SEMARANG - Aprilia Listiarini; Baju Widjasena; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2016)
Back pain is a phenomenon that often encounter in everyday life. One of the causes of back pain are manual handling. Porter in Tawang Station still using manpower without any supporting tools on doing their job. Lift transport job, like what porter did, the burden lies in the muscles especially on the back. This study aimed to analyze the relationship between back muscle strength and back pain of porter in Tawang Station on 2016. This study is a quantitative research with cross sectional design.The instrument used is the Body Map (to collect personal data such as age, years of service, smoking habits, and exercise habits also complaints of pain on body part) and Back Leg Chest Dynamometer (to measure the strength of the back muscles). The study population was the entire porter Tawang Station in total 60 people. Determination of the study sample using purposive sampling technique, which we did not measure if the back pain radiating to the leg because there’s a probability diagnozed of Herniated Nucleus Pulposus (HNP) and the measurement feared would make the condition even worse. From these techniques was obtained 57 respondents.The results showed that there was significant relation between back muscle strength and back pain complain of porter in Tawang Station. Spearman Rank correlation test results, confidence level of 95%, p = 0.001 (p <0.05) and the correlation coefficient r = -0.412. Therefore, it’s necessary to do back muscle strengthen exercise, exercising and strecthing regularly to maintain back flexibility which then would minimize the risk of back pain.